Roller ski rolling resistance and its effects on elite athletes` performance - Ainegren, M.; Carlsson, P.; Tinnsten, M. (Sports Engineering, 2009)
Modern ski-treadmills allow cross-country skiers, biathletes and ski-orienteers to test their physical fitness in a laboratory environment whilst performing classical and freestyle (skating) techniques on roller skis. For elite athletes, the differences in performance between test occasions are quite small, thus emphasising the importance of knowing the roller skis` rolling resistance in order to allow the correct comparison between the results of different test occasions. In this study, the roller skis` rolling resistance was measured on the ski-treadmill`s surface using a roller ski rolling resistance measurement system specially produced for this purpose. The study investigated the influence of significant changes in rolling resistance on physiological variables. The results showed that during submaximal exercise, power, oxygen uptake, heart rate and blood lactate were significantly changed by different rolling resistances, while there were no significant or only small changes to cycle rate, cycle length and ratings of perceived exertion. Incremental maximal tests showed that time to exhaustion was significantly changed by different rolling resistances and this occurred without significant changes in maximal power, maximal oxygen uptake, maximal heart rate and blood lactate, and that the influence on ratings of perceived exertion were insignificant or small.